The use of FTA to evaluate the potential of BIM platform in building rehabilitation - Fabiana Dias da Silva; Mônica Santos Salgado (PARC: Pesquisa em Arquitetura e Construção, 2017)
Several studies recognize the potential of interventions in existing buildings to reduce the consumption of natural resources and the use of new lands. In the context of sustainable design, the adoption of alternatives to support the integrated design and collaborative work - as Building Information Modeling (BIM) - offers a great potential to identify and propose interventions that implement sustainable practices equally - in new buildings as well as in the rehabilitation of existing ones. A case study was performed on the rehabilitation design process of the headquarters of PETROBRAS, in the city of Rio de Janeiro. The main purpose was to identify the potential of the BIM Platform for the improvement of the environmental performance of the building - one of the exigencies of the rehabilitation process - which had considered the requirements of the AQUA HQE environmental assessment and the Brazilian program of energy efficiency, the PROCEL EDIFICA, as its parameters. However, there was little integration among the design team and the BIM model. This article presents the results of the analysis of BIM Platform used in the design rehabilitation process of the given building, by using the FTA – the Fault Tree Analysis Method. The results indicate that BIM had not been considered from the beginning and the consequence was the low integration of the design process. BIM functionalities could, in turn, have brought more dynamism and integration to the design management process. Therefore, it is necessary to review the design process, in order to incorporate BIM potentialities since the beginning of the process and allow the collaborative work.